Standard monitor measurements EMP and LA-ICPMS (Table 4) - Kutterolf, Steffen; Freundt, Armin; Hansteen, Thor H; Dettbarn, Rebecca; Hampel, Fabian; Sievers, Carina; Wittig, Cathrin; Allen, Sharon R; Druitt, Timothy H; McPhie, Jocelyn; Nomikou, Paraskevi; Pank, Katharina; et al. (In: Kutterolf, S et al. (2021): Major and trace elements of Aegean Arc tephras [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.938615, 2021)
This datasets represents the microprobe reference measurements on Lipari and VGA99 with respective reference values as well as List standard N612 and BCR2 for trace element measurements. First column names the measured standard material, reference values are given for Lipari, VGA99, NIST612 and BCR. Microprobe standard monitor measurements are given from row 6 to 513. Below each species of standard material the average of all measurements is given, with STD in % the intrasample variation, and with 1SIG error the deviation to the literature data in % when comparing the average measured value with the reference values.
Keywords: Major and Trace elements Aegean land tephra; reference glass measurements